Knowledge, use and traditional management of wildlife in the community of Zoquital, Morelos, Mexico - Bello Román, Mónica; García Flores, Alejandro; Pino Moreno, José Manuel (Ethnobiology and Conservation, 2023)
Through their traditional productive activities, peasant and indigenous communities have generated knowledge on the use and management of wildlife to satisfy their needs for food, medicine or even to complement their basic food basket through the marketing of the species. The objective of this research was to analyze the knowledge, use and traditional management of wildlife in a rural community in the southwestern part of the state of Morelos, Mexico. The methodology included participant observation, semistructured interviews and guided tours and methods for obtaining and analyzing quantitative data “such as analysis of variance, a Mann‒Whitney U test and X2 test”. The interviewees recognized a total of 57 species of wildlife, of which 22 are used as food, medicine, ornament, amulets, furs and agricultural tools in four traditional production units. In addition, eight species were reported in the oral tradition. Four hunting techniques and five weapons were documented, with the shotgun being the most commonly used. Two factors regulate hunting in the community: the closed season and religion. A total of 62,454 kg of useful biomass was recorded, with mammals being the group that contributed the most kilograms, followed by reptiles and birds. There were no significant differences in species consumption, across months or rainy and dry seasons due to factors regulating hunting. Based on the total value index of the species, Odocoileus virginianus was the most important for the inhabitants of the community.